First Report of Molecular Identification of Prototheca zopfii Genotype 2 as Causative Agent of Bovine Mastitis in Navsari, South Gujarat, India - Makwana, Pushpa M; Patel, Dharmesh R; Prasana, Dixit K; Parmar, Saurabh R; Kalyani, Irsadullahkhan H.; Pal, Mahendra (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Prototheca species is emerged as an important causative agent for bovine mastitis worldwide, and is responsible for great economic losses for dairy industry. A 5-year-old HF cow was referred to the Veterinary Clinical Complex of the College, Navsari (India) with a complaint of watery milk with flakes, anorexia and drop in milk production. On physical examination, udder appeared warm and swollen, while milk consistency was thin, watery with flakes. Milk sample obtained aseptically from the cow was inoculated aerobically on Sabouraud dextrose agar and blood agar plates.  Prototheca colonies grew in pure and luxuriant form from mastitic milk on both the plates after 48 h of incubation. Prototheca zopfii was identified on the basis of colony morphology, staining characters and biochemical reactions. Molecular confirmation of Prototheca zopfii genotype 2 was performed by employing polymerase chain reaction (PCR). This report presents first isolation and molecular identification of Prototheca zopfii genotype 2 from a case of bovine mastitis from Navsari region, South Gujarat, India.
Keywords: Algae; Blood agar; Mastitis; PCR; Sabouraud medium